Millets, dogs, pigs and permanent settlement: productivity transitions in Neolithic northern China - Chris J. Stevens; Yijie Zhuang; Dorian Q. Fuller (Evolutionary Human Sciences)
The transition to sedentary agricultural societies in northern China fuelled considerable demographic growth from 5000 to 2000 BC. In this article, we draw together archaeobotanical, zooarchaeological and bioarchaeological data and explore the relationship between several aspects of this transition, with an emphasis on the millet-farming productivity during the Yangshao period and how it facilitated changes in animal husbandry and consolidation of sedentism. We place the period of domestication (the evolution of non-shattering, initial grain size increase and panicle development) between 8300 and 4300 BC. The domestication and post-domestication of foxtail (Setaria italica) and broomcorn (Panicum miliaceum) millet increased their productivity substantially, with much greater rate of change than for rice (Oryza sativa). However, millets are significantly less productive per hectare than wet rice farming, a point reflected in the greater geographical expanse of northern Neolithic millet cultures (5000–3000 BC) in comparison with their Yangtze rice-growing counterparts. The domestication of pigs in the Yellow River region is evidenced by changes in their morphology after 6000 BC, and a transition to a millet-based diet c. 4500–3500 BC. Genetic data and isotopic data from dogs indicate a similar dietary transition from 6000 to 4000 BC, leading to new starch-consuming dog breeds. Significant population increase associated with agricultural transitions arose predominately from the improvement of these crops and animals following domestication, leading to the formation of the first proto-urban centres and the demic-diffusion of millet agriculture beyond central northern China between 4300–2000 BC.